Government Collaboration on Controlling Illegal Mining in West Nusa Tenggara Province - Gede Harimbawa; I Nyoman Sumaryadi; Djohermansyah Djohan; Deti Mulyati (Budapest International Research and Critics University, 2022)
Illegal mining problems arise because the Mining Business Permit (IUP) has expired, so that miners who were originally licensed because the IUP has expired are reluctant to renew them so that they become